A third order Nakashima type implicit Pseudo Runge-Kutta method for delay differential equations - Lim, Tian Hwee (Universiti Kebangsaan Malaysia, 2014)
A third order Nakashima type implicit Pseudo Runge-Kutta method is presented. The free parameter was determined by minimizing the error bound. The stability region of the method was presented. Some problems on delay differential equations are tested to compare the accuracy of the proposed method with third order RADAU I.